The long run decline in employment participation for Australian public housing tenants: an investigation - Wood, G.; Ong, Rachel; Dockery, Alfred Michael (Routledge, 2009)
In the 20 years from 1982 to 2002, the proportion of Australian public housing tenants in employment has fallen markedly relative to Australians living in other housing tenures. This paper explores the potential causes of this trend and their policy implications. For male public renters, the declining employment participation rate can be accounted for by closer targeting of public housing to the most disadvantaged in the labour market and blunter work incentives. This is not the case for female public renters. Their employment participation rate has remained flat while improved labour market conditions should have lifted employment participation rates among this group, even after controlling for an extensive range of individual characteristics. Work incentives are important to female public renters, but further research is required if we are to understand why their employment rates have not improved over this 20-year period.